TAIWAN GASTRO-TOURISM: STRATEGI UNTUK MENINGKATKAN JUMLAH WISATAWAN TAHUN 2010-2017 - Sutawan, Putu nathania Krissandini; Kumala Dewi, Putu Ratih; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 2 (2024): JURNAL DIKSHI, 2024)
Abstract This study aims to describe Taiwan's gastro-tourism strategy in increasing the number of tourists from 2010 to 2017 using a qualitative-descriptive research method. Gastro-tourism is an important strategy in branding a country. Taiwan as a country that is not recognized as a sovereign country because of the One China Policy makes Taiwan have a weak status internationally. Therefore, Taiwan uses food as a nation branding tool to show its existence in international eyes as an attraction in tourism so that Taiwan sees the potential for gastro-tourism to have an impact on increasing the number of tourists and indirectly this proves that Taiwanese culture and food have received recognition. and the good image of the country. Using the time to eat program strategy, strategies through the media, through festivals, through OTOP and also through halal food proves that this strategy can increase the number of tourists quite significantly from year to year. So this study concludes that an effective strategy, the existence of consistent support from the government and the community is an important factor in developing gastro-tourism.     Keywords: Gastro- tourism, Food Taiwan,Tourism,Tourist